Pengaruh Kualitas Produk Terhadap Kepuasan Pelanggan Bingka Nayadam Batam - Rindu Nadia Dewi; Rahmat Hidayat (Politeknik Negeri Batam, 2015)
Customers have become more selective in determining the quality of a given product to achieve customer satisfaction. Product quality can usually be measured with brands and packaging. The purpose of this study was to analyze the effect of eachs variable, brand (X1), packaging (X2) on customer satisfaction (Y) bingka Nayadam Batam. Samples in this study of 100 respondents and by using non-probability sampling technique sampling is purposive sampling. This research using program SPSS 20.0. The analysis technique using validity, reliability, classical assumptions with hypotheses and multiple linear analysis. The results were obtained brand variables significantly influence customer satisfaction Bingka Nayadam Batam. Variable packaging also significantly influence customer satisfaction Bingka Nayadam Batam. Brand and packaging simultaneously significant effect on customer satisfaction Bingka Nayadam Batam. The variable most dominant influence on customer satisfaction Bingka Nayadam Batam is the packaging. Figures Adjusted R square of 0.555 indicates that 55.5% customer satisfaction can be explained by two independent variables used in the regression equation. While the remaining 44.5% is explained by other variables that are not included in this research model.